Effects of corporate governance and financial performance on fraudulent financial statements: evidence from Indonesia’s property, real estate, and building construction sectors / Reni Yendrawati , Reny Lia Riantika, Firkhansya Zuhaira Kusumadewi , Nurul Azlin Azmi and Zuraidah Mohd Sanusi - Yendrawati, Reni; Raintika, Reny Lia; Kusumadewi, Firkhansya Zuhaira; Azmi, Nurul Azlin; Mohd Sanusi, Zuraidah (UiTM Press, 2023)
This study aimed to examine the effects of managerial and institutional ownership, and financial performance on fraudulent financial statements. Companies with weak governance and poor financial performance have a high tendency to partake in fraudulent activities as these factors create pressure and opportunity (fraud triangle theory) to mask financial figures. Weak governance sectors were chosen from the Indonesia Stock Exchange property, real estate, and building construction sectors. This study used a purposive sampling technique with predetermined criteria and employed panel regression analysis. The final panel data set consisted of 96 company-year observations. Managerial and institutional ownership had a significant and negative effect on fraudulent financial statements. Company leverage had a positive and significant relationship with fraudulent financial statements. Nevertheless, company profitability had no association with fraudulent financial statements. Furthermore, the interaction of company profitability strengthened the positive effect of managerial ownership and fraudulent financial statements. This study contributes to the literature by examining the corporate governance effectiveness in curbing fraudulent financial statements in selected sectors in Indonesia. In addition, this study offers practitioners insights into enhancing the effectiveness of internal and external governance mechanisms as well as the internal control systems in the companies.